Factors Associated with Dynamic Changes in Japanese Agriculture: Farm Discontinuation and Entry Using the Individual 2005 and 2010 Census of Agriculture - Kurihara, Shinichi; Shimoura , Shimpei; Maruyama , Atsushi; Luloff , A. E (Asian Journal of Agriculture and Rural Development, 2013)
Using descriptive and quantitative analyses of farming households drawn from the 2005 and 2010 censuses of agriculture, this study provides reference material for future efforts to support agriculture and agricultural communities. Despite some data limitations for a few municipalities, several significant trends were identified. Discontinued farm households (those that ceased commercial activities between the two Censuses) tended to be in the Hokuriku region. These farms were characterized by aging populations, lack of successors, and a decline in operation size. Further, they tended to rent their farmland and had low rates of environmental conservation practices – both signal indicators of diminished capacity as operators in regional agriculture. Moreover, although no clear trends were identified among entrant farm households (those that began commercial agricultural operations during the same period), it is notable that they shared characteristics with discontinued farm households, such as being small scale operations and lacking successors. The current shortage of fiscal budget allocated to agriculture necessitates a narrowing and/or prioritization of support efforts. In this context, these results may enable the development of efficient measures to prevent farm discontinuation and to assist the emergence of entrant farm households.